Nitrogen, Phosphorus, and Carbon Concentrations in Some Common Aquaculture Feeds - Sirirat Chatvijitkul; Claude E. Boyd; D. Allen Davis (the World Aquaculture Society, 2025)
Nitrogen, phosphorus, and carbon concentrations were measured from 203 samples of starter, fingerling, and grower aquaculture feeds from several countries and for several common species. The feed protein concentrations reported by manufacturers often were slightly greater than the measured crude protein concentrations. The correlation coefficients (R2) between feed nitrogen and carbon concentrations were less than 0.50, and nitrogen and phosphorus concentrations in feed were not correlated. There were considerable differences in elemental concentrations among feeds, but the overall averages for carbon, nitrogen, and phosphorus concentrations, respectively, were as follows: starter feed 41.36, 7.78, and 1.57%; fingerling feed 39.75, 5.95, and 1.36%; grower feed 39.97, 5.36, and 1.22%. Concentrations of carbon, nitrogen, and phosphorus in feeds are required in estimating the pollution potential of aquaculture facilities. The crude protein concentration – if provided by the manufacturer – can be used to estimate nitrogen concentration in feed, but carbon and phosphorus concentrations should be measured.